19. The Effect of AKBIS Probiotic Adding that Fermented in Fodder toward the Total of Aspergillus niger of Broiler’s Gastrointestinal Tract - Cut Lathifa Nurrady; Nurliana Nurliana; Safika Safika; T. Reza Ferasyi; Ismail Ismail; Muttaqien Muttaqien (Jurnal Medika Veterinaria, 2018)
This study aimed to determine the total of A. niger found in the gastrointestinal tract of broilers after the addition of soybean dregs and fermented palm kernel meal by A.niger as probiotics (AKBIS Prob) in the fodder. This study used a complete randomized factorial design, which consists of two factors, namely factor AKBIS concentration and duration of AKBIS Prob. The treatment was divided into the group as a control P0, P1, P2 and P3 which consisted of five broilers, respectively given feed supplemented with AKBIS Prob 2, 4 and 6%. The provision of AKBIS Prob has done for 21 days and 35 days. On the 22nd and 36th day the contents of the caecum were taken. The total of A. niger was obtained using Total Plate Count (TPC) method. The data analysis used a factorial analysis of variance. The results showed that the concentration of 2, 4 and 6% did not affect (P 0.05) the total of A. niger in the caecum of broilers, while the provision of AKBIS prob in fodder for 21 and 35 days had a significant effect (P 0.05) to the total A. niger. It can be concluded that the provision of the concentration of AKBIS Prob up to 6% in the fodder decreases the total of A. Niger. The provision of AKBIS Prob for 35 days can increase the total of A. niger in the digestive tract of broilers.